A cooperação judiciária interinstitucional como estratégia de participação da sociedade na administração da justiça: elementos para uma concertação entre o TRT1 e o Ninter Rodorio - Bárbara Deming Leão Brandão (2023)
The research is part of the collective project “Access to Justice through rights, digital justice, public governance, administration of justice, legal hermeneutics and fundamental rights” and in the line of research “Human Rights and the Democratic Rule of Law: Foundations, Participation and Effectiveness”, from the Postgraduate Program in Law at the Federal University of Minas Gerais (UFMG). The theme of the investigation is the participation of the Inter-Union Center for Labor Conciliation of Urban Transport of the Municipality of Rio de Janeiro (Ninter Rodorio) in the organization of work and the administration of labor justice within the scope of the Regional Labor Court of the 1st Region (TRT1 - Rio de Janeiro), made possible by the signing of a judicial cooperation agreement (Resolution no. 350/2020, of the CNJ). Ninter Rodorio is a private law entity created based on article 625-H, of the Consolidation of Labor Laws (CLT). It results from collective negotiation between the Union of Workers in Urban, Intermunicipal, Interstate, Charter, Tourism, School, Cargo, Logistics and Differentiated Passenger Road Transport Companies of the Municipality of Rio de Janeiro (Sintrucad-Rio) and the Union of Transportation Companies Rio de Janeiro City Bus (Rio Ônibus), aiming to meet common interests related to collective bargaining, dialogue, social consultation, prevention and resolution of labor conflicts. The research problem consists of asking whether the Ninter Rodorio is aligned with the judicial policies of the National Council of Justice (CNJ) and the Superior Council of Labor Justice (CSJT) and whether the Center can contribute, through the celebration of the term of interinstitutional judicial cooperation, for the implementation of the National Judiciary Strategy within the scope of TRT1. The guiding hypothesis of the research is that Ninter Rodorio is aligned with the judicial policies of the CNJ and CSJT and that it can contribute to the execution of the National Judiciary Strategy at the local level. This preliminary response is based on the practice of permanent collective bargaining in the Ninter Tripartite Council. Primary and secondary research sources were used. As a result, it was found that the institutional practices provided for in the Ninter Rodorio statute, with regard to the prevention and resolution of labor conflicts, converge with the judicial policies outlined in the National Strategy for the Judiciary in its developments within the scope of the Regional Court of Work of the 1st Region (TRT1 - Rio de Janeiro), and that judicial cooperation constitutes a strategic instrument for the concertation of consensual criteria for validating the acts carried out by Ninter Rodorio by the local Judiciary. This presupposes that Ninter Rodorio acts in accordance with its statute, the Constitution of the Republic and labor legislation. Thus, as a purposeful product of the research, an outline of a possible judicial cooperation agreement is presented, to be concluded between the parties, addressing issues considered relevant for this purpose.